2010
DOI: 10.1375/twin.13.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Genome-Wide Linkage Scan of Subjective Happiness

Abstract: C auses of individual differences in happiness, as assessed with the Subjective Happiness Scale, are investigated in a large of sample twins and siblings from the Netherlands Twin Register. Over 12,000 twins and siblings, average age 24.7 years (range 12 to 88), took part in the study. A genetic model with an age by sex design was fitted to the data with structural equation modeling in Mx. The heritability of happiness was estimated at 22% for males and 41% in females. No effect of age was observed. To identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 39 publications
2
35
0
6
Order By: Relevance
“…Basada en las investigaciones existentes, Lyubomirsky cree que el componente genético puede explicar hasta el 50% de la felicidad, que nuestras circunstancias solo impactan el 10% de la felicidad y que el 40% depende de nuestra voluntad, de nuestras decisiones, actitudes y acciones. Otros autores han encontrado que el factor genético explica menos de la mitad de la felicidad (entre el 22% y el 40%) (Bartels et al 2010), pero parece haber un consenso respecto a que una buena parte de nuestro bienestar está en nuestras manos.…”
Section: Las Fortalezas De Carácterunclassified
“…Basada en las investigaciones existentes, Lyubomirsky cree que el componente genético puede explicar hasta el 50% de la felicidad, que nuestras circunstancias solo impactan el 10% de la felicidad y que el 40% depende de nuestra voluntad, de nuestras decisiones, actitudes y acciones. Otros autores han encontrado que el factor genético explica menos de la mitad de la felicidad (entre el 22% y el 40%) (Bartels et al 2010), pero parece haber un consenso respecto a que una buena parte de nuestro bienestar está en nuestras manos.…”
Section: Las Fortalezas De Carácterunclassified
“…. Le bonheur, tel qu'il est mesuré dans cette étude, apparaît donc lié de manière 4 Rappelons que le gène est porté par le chromosome X. 5 Ces derniers chiffres se réfèrent à la fraction de déviation standard, mais comme celle-ci est très proche de 1 (0,97), ils expriment aussi l'incrément de bonheur en valeur absolue.…”
Section: De Quoi S'agit Il ?unclassified
“…Après ces corrections (qui tiennent aussi compte de la santé physique, de l'âge et même de la « religiosité »), l'effet reste nul chez les hommes et notable chez les femmes : plus 0,261 pour un allèle MAOA-L et 0,522 pour deux 5 . Le bonheur, tel qu'il est mesuré dans cette étude, apparaît donc lié de manière 4 Rappelons que le gène est porté par le chromosome X. 5 Ces derniers chiffres se réfèrent à la fraction de déviation standard, mais comme celle-ci est très proche de 1 (0,97), ils expriment aussi l'incrément de bonheur en valeur absolue.…”
Section: De Quoi S'agit Il ?unclassified
See 1 more Smart Citation
“…It was found that heritability could be accounted for up to 40-50% of the variance of subjective well-being (Lykken & Tellegen, 1996;Stubbe, Posthuma, Boomsma & Geus, 2005). A study on twins and siblings also found that the heritability of happiness was estimated at 41% in females and 22% for males (Bartels, Saviouk, Moor, Willemsen, Beijsterveldt, Hottenga, Geus & Boomsma, 2010). In the current research, although genetic influences on subjective well-being and materialism were not measured and evaluated, it is to be noted that the effect of heritability or genetic factor should not be disregarded.…”
Section: Limitations and Recommendations For Future Studymentioning
confidence: 96%